Isolation, identification and oenological characterization of non‐Saccharomyces yeasts in a Mediterranean island. (August 2016) - Polizzotto, G.; Barone, E.; Ponticello, G.; Fasciana, T.; Barbera, D.; Corona, O.; Amore, G.; Giammanco, A.; Oliva, D.
Abstract: We isolated, identified and characterized yeast strains from grapes, and their fermented musts, sampled in the small island of Linosa, where there are no wineries and therefore the possibility of territory contamination by industrial strains is minimal. By traditional culture‐dependent methods, we isolated 3805 colonies, distinguished by molecular methods in 17 different species. Five hundred and forty‐four isolates were analysed for the main oenological characteristics such as fermentative vigour with and without sulphites, sugar consumption and production of alcohol, volatile acidity, hydrogen sulphide, glycerol and β‐glucosidase. This analysis identified Kluyveromyces marxianus (seldomly used in winemaking) as the most interesting candidate yeast for the production of innovative wines. Significance and Impact of the Study: In recent years, interest is growing for wine production by non‐ Saccharomyces yeasts, both in research and in the industry. This study describes the yeast population of the grapes in a small‐secluded island in the Mediterranean Sea, useful site for the search of new strains. Evaluation of fundamental oenological characters identifies potential best yeasts to assay in experimental vinifications. We also describe, for the first time, 14 new colony morphologies on WL Nutrient Agar, culture medium used to monitor the yeast population dynamics. Abstract : Significance and Impact of the Study: In recent years, interest is growing for wine production by non‐ Saccharomyces yeasts, both in research and in the industry. This study describes the yeast population of the grapes in a small‐secluded island in the Mediterranean Sea, useful site for the search of new strains. Evaluation of fundamental oenological characters identifies potential best yeasts to assay in experimental vinifications. We also describe, for the first time, 14 new colony morphologies on WL Nutrient Agar, culture medium used to monitor the yeast population dynamics.